(untitled) (Pravaha, 2025)
The efficient processing and dissemination of information are fundamental to the proper functioning of a stock market, as they directly affect capital allocation and economic growth. This study investigates the Random Walk Hypothesis (RWH) in the Nepalese stock market by analyzing daily NEPSE Index returns from March 2011 to March 2020. Utilizing both parametric and non-parametric tests—including the Kolmogorov-Smirnov test, run test, autocorrelation, autoregression, Augmented Dickey-Fuller test, ARIMA modeling, and variance ratio test— the study consistently finds evidence against the RWH. The results reveal that NEPSE returns are not independently and identically distributed, indicating weak-form inefficiency. This suggests that historical price movements can predict future returns, highlighting significant market inefficiencies and potential opportunities for abnormal gains. However, such inefficiencies also increase investor vulnerability to misinformation, manipulation, and risk. The findings align with similar outcomes in emerging markets and challenge the universal applicability of the Efficient Market Hypothesis (EMH). Furthermore, the study underscores the growing importance of behavioral finance in explaining stock price dynamics in underdeveloped markets. It offers crucial insights for policymakers, researchers, and investors focused on enhancing the Nepalese capital market’s efficiency.